Harakah dan Kemandirian Perempuan - Muhammad Mukhtar (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
Women have equal access to men in their role in society. The macro context, which is entirely different, has an impact on the problem of the interpretation of the Koran as a whole and specifically concerning the harakah and independence of women. The Koran does not say that all men have more advantages than all women. But the Koran says "some of you over others outperform". Some men excel over some women and vice versa. The view that expresses male superiority towards women and limits the need for women only to the domestic aspect should consider macro contexts in the past with their current macro context. To realize the dignity and independence of women and to preserve their rights, nature, and identity, women are required to be aware of their potential and prove their ability in the real world.